Cordycepin, a Characteristic Bioactive Constituent in Cordyceps militaris, Ameliorates Hyperuricemia through URAT1 in Hyperuricemic Mice - Yong, Tianqiao; Chen, Shaodan; Xie, Yizhen; Chen, Diling; Su, Jiyan; Shuai, Ou; Jiao, Chunwei; Zuo, Dan (Frontiers in Microbiology, 2018)
Recently, we’ve reported the anti-hyperuricemic effects of Cordyceps militaris. As a characteristic compound of C. militaris, we hypothesised that cordycepin may play a role in preventing hyperurecimia. Remarkably, cordycepin produced important anti-hyperuricemic actions, decreasing SUA (serum uric acid) to 216, 210 and 203 μmol/L (P<0.01) at 15, 30 and 60 mg/kg in comparison of hyperuricemic control (337 μmol/L), closing to normal control (202 μmol/L). Elisa, RT-PCR and western blot analysis demonstrated that the actions may be attributed to its downregulation of uric acid transporter 1 (URAT1) in kidney. Serum creatinine levels and blood urine nitrogen and liver, kidney and spleen coefficients demonstrated that cordycepin may not impact liver, renal and spleen functions. In addition, we used computational molecular simulation to investigate the binding mechanism of cordycepin. Of which, van der Waals interaction dominated the binding. Residues TRP290, ARG17, ALA408, GLY411 and MET147 contributed mainly on nonpolar energy. This provided the theoretical guidance to rationally design and synthesis novel URAT1 inhibitors.